PENGARUH HARGA EMAS, MINYAK, BATU BARA DUNIA, DAN VARIABEL MAKROEKONOMI TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR BATU BARA DI BEI (2020–2024) - Angga Hergastyasmawan; Ellen D Oktanti Irianto (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This study aims to analyze the impact of global commodity prices and macroeconomic variables on the stock prices of coal subsector companies in Indonesia during the period 2020–2024. Using secondary data, this research applies panel data regression with the Random Effect Model (REM). The independent variables analyzed include the world gold price, world oil price, world coal price, interest rates, USD/IDR exchange rate, inflation, and foreign exchange reserves. The results show that only world oil prices and the USD/IDR exchange rate significantly affect the stock prices of coal companies. The increase in world oil prices boosts global energy demand, making coal a more sought-after and affordable alternative fuel. This leads to higher demand for coal, which in turn drives up the stock prices of coal companies. Meanwhile, the strengthening of the US dollar increases the export revenue of companies in rupiah, improving their financial performance and stock prices. On the other hand, world gold prices, world coal prices, interest rates, inflation, and foreign exchange reserves do not significantly affect stock prices. These findings provide insights for investors and policymakers to monitor external factors that influence the coal subsector.